Presentation (Prassi Ecdotiche della Modernità Letteraria, 2016)
The section welcomes contributions that deepen textual, philological, ecdotic or historical-critical issues, or that specify the state of the studies on texts dating from the XVIIIth to XXth centuries, with the aim of favoring the comparison and the methodological exchange.